DERERMINANTS OF ISLAMIC BOND MARKET REACTION Empirical Study of Islamic Bond in Indonesia - Sutrisno Sutrisno; Rahayu Ningtiyas (Jurnal Apresiasi Ekonomi, 2021)
The main objective of this study is to examine several factors that cause islamic bonds market reaction as measured by cumulative abnormal return. The factors that are believed to be the determinants of islamic bond market reaction are the value of islamic bonds issuance, islamic bond rating, age of islamic bonds and size of the islamic bond issuing company. The population in this study are companies that issue Islamic bonds and are listed on the Indonesia Stock Exchange with a four-year observation period (2015-2018). The sample selection in this study uses purposive sampling based on certain criteria. In sample selection 36 Islamic bonds were obtained as samples. This study uses secondary data where the data is obtained from the annual report and the website of the issuing company. To test the hypothesis, using a multiple regression analysis tool with a significance level of 0.05. The results showed that the value of Islamic bonds issuance and rating of Islamic bonds issuance had a positive effect on market reaction. While the age of islamic bonds and the firm size have no effect on the reaction of the islamic bond market